Penerapan Proyek Penguatan Profil Pelajar Pancasila Melalui Kegiatan Market Day Dalam Membentuk Karakter Gotong Royong Anak Usia 5-6 Tahun - Arifinata, Citra Ayuda; Kristiana, Dian; Rusdiani, Nurtina Irsad (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
This research explores the implementation of project-based learning at Dharma Wanita Demangan Kindergarten to cultivate the Pancasila student profile, specifically focusing on instilling mutual cooperation from an early age. The study posits that such learning strengthens positive social character through immersive experiences, potentially shaping children's future social interactions. Employing a qualitative descriptive approach, data was collected via observations of the principal, a teacher, and student learning, alongside interviews and documentation of the teaching process. The analysis involved data collection, reduction, presentation, and conclusion drawing. Findings indicate that the Market Day project was successfully implemented and fostered elements of mutual cooperation among children. This success was attributed to student enthusiasm, parental support, and the teacher's creative teaching methods. However, the study also identified the dominance of certain children as a challenge requiring teacher intervention to ensure equitable participation.Ultimately, this research contributes to understanding the practical application of project-based learning in early childhood education to enhance the Pancasila student profile, particularly in nurturing mutual cooperation. It also highlights key factors influencing the effectiveness of such initiatives.